Pelatihan Keterampilan Menulis Ilmiah bagi Mahasiswa Semester Akhir - Suratni Suratni; Milcha Handayani Tammubua; Rivaldhy N. Muhammad; Muhammad Sawir; Fredrik Sokoy; Rif’iy Qomarrullah; Lestari Wulandari (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Scientific writing skills are essential for final-year students in completing academic assignments and enhancing their competitiveness in both academic and professional fields. However, many students face challenges in producing scientific papers that meet academic standards, particularly in terms of structure, language, and analysis. This study aims to improve students' scientific writing skills through structured training. The method used in this program is practice-based training with an interactive approach, including workshops, mentoring, and direct evaluation of participants' writing. The program targeted a group of 40 final-year students from various academic disciplines, who participated in a series of workshops and one-on-one mentoring sessions. Data were collected through pre- and post-training assessments of writing quality, including structure, coherence, and argumentation. The results indicate that after attending the training, students showed significant improvement in understanding the structure of scientific papers, mastering effective writing techniques, and developing data-based arguments. The post-training assessments showed an increase of 30% in the average quality of the students’ writing. The implications of this study suggest that scientific writing training can be an effective strategy in preparing competitive academic human resources capable of contributing to scientific publications. Additionally, these findings highlight the importance of providing structured and interactive training programs to enhance students’ academic writing skills.